(untitled) (Journal of Human Sciences, 2026)
This study examines the Italo-Libyan War (1911–1912) through the coverage of the French newspaper Le Figaro, one of the leading European newspapers of the time. The research aimed to analyze how the war was represented in the French media, focusing on its military, political, and diplomatic dimensions, as well as the portrayal of the warring parties and the local population. The findings reveal that Le Figaro presented the war within a European colonial framework, justifying Italy’s intervention under the pretexts of “modernization” and “civilization,” while paying greater attention to international reactions—particularly those of France, Britain, and Germany—than to the internal Libyan context. The study also shows that. The research highlights the significance of press sources in understanding modern Libyan history and underscores the role of European media in constructing colonial legitimacy and shaping public opinion regarding struggles for national liberation.